Methods in astrodynamics and celestial mechanics - Astrodynamics Specialist Conference (1965 : Monterey, California); Duncomber, Raynor L.; Szebehely, Victor Groyzo, 1921-; American Institute of Aeronautics and Astronautics; Institute of Navigation (New York : Academic Press, 1966)
19